2016
DOI: 10.3846/16484142.2016.1247295
|View full text |Cite
|
Sign up to set email alerts
|

Merging process of U-turns at uncontrolled median openings under mixed traffic conditions

Abstract: Merging process of U-turns at uncontrolled median openings under mixed traffic conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The speed at which a vehicle merges into a gap is an essential parameter to judge the driver's behaviour. The merging could be possible when the available gap is sufficiently large (greater than the critical gap); otherwise, vehicles should wait for the next suitable gap (Sil et al, 2016). Contrary to this norm, the behaviour of motorcyclists in the study area was found to be quite disruptive and impolite.…”
Section: Effect Of Approach Speed On Gap Acceptancementioning
confidence: 89%
“…The speed at which a vehicle merges into a gap is an essential parameter to judge the driver's behaviour. The merging could be possible when the available gap is sufficiently large (greater than the critical gap); otherwise, vehicles should wait for the next suitable gap (Sil et al, 2016). Contrary to this norm, the behaviour of motorcyclists in the study area was found to be quite disruptive and impolite.…”
Section: Effect Of Approach Speed On Gap Acceptancementioning
confidence: 89%
“…The U-turn is the maneuver of a vehicle that makes a 180 • turn in a specific area to reverse its direction [1]. Vehicles that need to make U-turns often create merging points with traffic approaching from other directions [2]. This not only reduces the efficiency and stability of the intersection but also increases the probability of accidents, taking into account the lane-changing and merging behavior of vehicles [3].…”
Section: Introductionmentioning
confidence: 99%
“…Menendez et al [16] developed delay equations that can be applied to assess uncontrolled roudabouts involving two or three conflicting [C] or non-conflicting streams [NC] and validated with the HCM [17] control delay model in Zurich, Switzerland. Sil et al [18] studied influence of service delay (SD) on U-turn merging time (MT) for five vehicle categories considering conventional and forced merging situations based on time-distance plots. The authors also studied the effects of opposing traffic flow on U-turn merging time at uncontrolled median openings.…”
Section: Introductionmentioning
confidence: 99%
“…Swift and gradual merging were found to significantly different from each other under mixed traffic. Guller and Menendez [18] determined delay of priority and non-priority conflicting streams for five uncontrolled traffic facilities (4 nos. intersections and 1 no.…”
Section: Introductionmentioning
confidence: 99%